The Influence of Speech Delivery Rates on Simultaneous Interpreter's Performance (Journal of the College of Basic Education, 2022)
The task of determining the factors that affect simultaneous interpreter's performance is rather difficult. By comparison with other fields on cognitive psychology, reported research on simultaneous interpretation (SI) is scarce. Perhaps the recent advent of this discipline is largely to blame, but also the complexity of the mental processes involved in SI has been a deterrent to researchers. It is not straight forward to design controlled experiments for the study of the cognitive processes concomitant with speech. It is doubly difficult to design such experiments for the study of simultaneous perception and production of speech in two different languages and the factors that affect the successful achievement of both.